Knowledge, Awareness and Attitude of Pharmacy Students towards Epilepsy in Iraq (Medico Legal Update, 2021)
Background: The undergraduate students in pharmacy colleges represent a well-educated group of thecommunity according to the use of drugs and they are required to hold the appropriate knowledge of druguse and have positive attitudes toward health problems, this good knowledge about the diseases and theirtreatment will give good pharmacists in the future and this will reflect positively on patient knowledge, andtheir compliance with treatment, this due to direct contact of pharmacists with the patients.Aim: To know the knowledge, Awareness and Attitude of a sample of Iraqi pharmacy students towardsepilepsy.Method: Cross-sectional study used a structured questionnaire validated by previous studies to collectdata about knowledge, Awareness and Attitude about epilepsy from all stages of undergraduate pharmacystudents, this survey involves 260 respondents from different universities in Iraq.Results: The questionnaire was responded by 260 students. The main part of the respondents were of agegroup between 21-25 years (84.2%). The majority of the respondents were female (67.3%), and (32.7%)were male. Overall knowledge was moderate (60.1±17.8), awareness was poor (42.6±33.5) but the attitudetoward epilepsy was very good (83.3±13.1).Conclusions: The results of this study showed that, majority of the students had knowledge of the diseasehowever, the knowledge score was moderate. While Awareness score was low, we need to have focusededucation and efforts to increase the knowledge and awareness towards epilepsy among pharmacy students.At the same time the attitudes of pharmacy students toward epilepsy in this study was very good.